The influence of financial education on consecutive debt-taking behaviour of low-income households in Indonesia - Arsyianti, Laily Dwi; Kassim, Salina (IIUM Press, 2017)
Debt is considered as one of the major sources of funds from third party, especially for low-income households. Even though Islam allows debt, it should not be used recklessly. Taking one debt after another is apparently not suggested for the low-income households although it is common among them. In order to understand the consecutive debt-taking behaviour among the low income households in Indonesia as well as the role of financial education in influencing this behaviour, this study adopts the Structural Equation Modelling (SEM) to analyse pertinent data elicited from 1,780 low-income households from six areas in Indonesia. The study finds that financial education has positive effect on using debt consecutively albeit wisely for fulfilling family needs. By wisely, it means that the low income households are able to control their desire and satisfaction, thus practicing the true spirit of consumption as proposed in Islam.